Interaction of vaginal microbiota and biomarkers in Premature rupture of membranes: from bench to beside - Deng, Yudi; Li, Yang; Liu, Tiana; Wu, Fuju (Frontiers in Immunology, 2025)
Preterm premature rupture of membranes (PROM) is a critical obstetric complication endangering maternal and neonatal health, with growing evidence linking vaginal microecology to its pathogenesis. This review synthesizes the relationship between vaginal microbiota and PROM risk, as well as microecology-targeted prevention and management strategies. A balanced vaginal microbiome, dominated by lactobacilli that maintain an acidic protective environment, is essential for reproductive health. Dysbiosis—marked by reduced lactobacilli and increased pathogens like Gardnerella and Atopobium—impairs local immunity, weakens fetal membranes, and elevates PROM risk, with bacterial vaginosis (BV) strongly associated with this condition. Pathogenic overgrowth activates inflammatory (via TLR-mediated IL-1β, TNF-α, IL-6 overproduction) and oxidative stress pathways: pro-inflammatory cytokines promote cervical ripening, induce matrix metalloproteinases (MMPs) to degrade fetal membrane collagen, while reactive oxygen species (ROS) directly damage structural proteins, compromising membrane integrity. Monitoring inflammatory/oxidative stress biomarkers (e.g., cytokine levels, ROS activity) enables early risk assessment. Potential interventions include probiotics to restore microbial balance, antioxidants/immunomodulators to counteract stress/inflammation, and MMP inhibitors to preserve membrane structure, all aiming to improve pregnancy outcomes. In conclusion, vaginal microecology plays a pivotal role in PROM development, underscoring the need for early microecological monitoring. Future research should dissect mechanistic complexities and develop precision tools for preterm labor management.